Two to tango: Public-private collaboration for productive development policies - Eduardo Fernández Arias; Charles F. Sabel; Ernesto Hugo Stein; Alberto Trejos (Inter-American Development Bank (IDB), 2017)
This paper summarizes the findings of the recent Inter-American Development Bank book Two to Tango: Public-Private Collaboration Productive Development Policies, based on case studies of 25 productive development policies (PDPs) in five countries and discusses an additional example from Peru. One finding that emerges from those studies is that governments could not make policy in isolation and needed private sector involvement at every phase of the policy process. It is also found that the private sector generally collaborated in the design and implementation of PDPs without attempting to manipulate or capture them. In contrast to previous views of PDPs as static and best undertaken in isolation by governments, successful PDPs involve a dynamic and interactive process with ample and continuous private sector participation.
Keywords: L52; O25; O54; 330; Productive development policies; Industrial policy; Policymaking process